FAKTOR-FAKTOR KEGAGALAN INDIA MENERAPKAN PRINSIP CEDAW (CONVENTION ON THE ELIMINATION OF ALL FORMS OF DISCRIMINATION AGAINST WOMEN) (STUDI KASUS: DISKRIMINASI PEREMPUAN KASTA DALIT) - Shirley Dwi Gayatri; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This researh analyzes the factors in India's failure to apply the principles of CEDAW (Convention on The Elimination of All Forms of Discrimination Against Women). The case study taken is discrimination against Dalit caste women in India. This research will look at the factors of India's failure in adopting the CEDAW convention policy in India's national policy which is oriented towards the goal of gender equality and the elimination of all forms of discrimination. Cases of discrimination against Dalit women have been going on for a long time but this practice is still continuing. Dalit women experience caste and gender discrimination simultaneously. Discriminatory practices against Dalit caste women in India clearly violate CEDAW principles. This research uses a qualitative method with data collection techniques, researchers use secondary data with document analysis data collection techniques referring to books, journals and internet sites. The state as the level of analysis and supported by regime effectiveness theory as a basic research reference. The results shows that India has failed to fulfill its obligation in applying CEDAW principles. The practice of discrimination that continues until now is proof of this failure, the number of discriminations against Dalit Women on average increases every year. In implementing CEDAW principles, India has used various instruments which include public policies in the form of regulations, sanctions, and capacity building through education and government programs. Government efforts have not had a significant impact.. India's failure to apply CEDAW principles is caused by several factors, namely social factors, cultural factors, economic factors, and justice factors. Keywords: Discrimination, Dalit, Caste, CEDAW, Women, India